A metal-oxide-semiconductor radiation dosimeter with a thick and defect-rich oxide layer. (17th March 2016) - Liu, Hongrui; Yang, Yuhao; Zhang, Jinwen
Abstract: Enhancing the density of defects in the oxide layer is the main factor in improving the sensitivity of a metal-oxide-semiconductor (MOS) radiation dosimeter. This paper reports a novel MOS dosimeter with a very thick and defect-rich oxide layer fabricated by MEMS technology. The category of defects in SiO2 and their possible effect on the radiation dose sensing was analyzed. Then, we proposed combining deep-reactive-ion etching, thermal oxidation and low pressure chemical vapor deposition to realize an oxide layer containing multiple and large interfaces which can increase defects significantly. The trench-and-beam structure of silicon was considered in detail. The fabrication process was developed for obtaining a thick and compact MEMS-made SiO2 . Our devices were irradiated by γ -rays of 60 Co at 2 Gy per minute for 2 h and a thermally stimulated current (TSC) method was used to determine the readout of the dosimeters. Results show that there is a peak current of about 450 nA, indicating a total TSC charge of 158 μ C and sensitivity of 1.1 μ C mm −3 ·Gy, which is 40 times the sensitivity of previous MOS dosimeters.